Ultrasound Guided Intra-Articular Injection of Triptolide-loaded Solid Lipid Nanoparticle for Treatment of Antigen-Induced Arthritis in Rabbits - Li, Shilin; Su, Liyang; Lv, Guorong; Luo, Weiwen; Kang, Yishan (Frontiers in Pharmacology, 2022)
Objective: To evaluate the efficacy of ultrasound-guided intra-articular injection of triptolide-loaded solid lipid nanoparticle (TP-SLN) for treatment of antigen-induced arthritis (AIA) in rabbits. Material and Methods: Knee joints of 33 New Zealand rabbits with AIA were injected intra-articularly with triptolide (TP: n = 7), TP-SLN (n = 7), betamethasone (BS: n = 7) and dimethyl sulfoxide (DMSO: n = 6). The remaining six rabbits were untreated as the control group. The injection therapy in intervention groups was initiated 1 week after the last immunization in order to avoid irreversible joint damage in the later induction. The ultrasonic scores of the joints were assessed based on synovitis, synovial blood flow and bone erosion. Meanwhile, the correlations of ultrasonic scores and pathological scores were determined. The efficacy and side effects of each group were determined by combining ultrasonic scores, pathological scores, behavior, appetite, weight, joint diameter, skin temperature and biochemical examination. Results: 1) Compared with the control group, the diameters of knee joints of the TP, TP-SLN and BS groups began to reduce 1 week after intra-articular injection (p < 0.01). 2) With the exception of the DMSO group, the interventions were effective in treating synovitis compared with the control group, with TP-SLN and BS being the best. The ultrasonic and pathological scores in synovitis of the TP group were lower than that of model group (Z = -2.726 and -2.530, p < 0.05). The ultrasonic scores differed significantly between BS group and TP-SLN group (Z = −2.17 and -2.360, respectively, p < 0.05) and pathological scores (Z = −2.687 and −2.082, respectively, p < 0.05). 3) Compared with the control group, the TP, BS and TP-SLN were all effective in treating synovial blood flow and bone erosion and there were no significant differences of ultrasonic and pathological scores among them (p > 0.05). The ultrasonic scores of synovial blood flow (Z = −3.033, −2.842, −3.277, p < 0.01) were lower than in the controls. The ultrasonic scores (Z = -2.948, -3.141, -3.210, p < 0.01) and pathological scores (Z = −2.216, −2.505, −2.505, p < 0.05) of bone erosion were also lower than in the model group.4) There were significant correlations between the ultrasonic and pathological scores of synovial inflammation and bone erosion (r = 0.832 and 0.859 respectively, p < 0.001). Conclusions: The therapeutic effect of TP-SLN on arthritis is better than that of TP, but there is no difference between BS and TP-SLN. Therefore, TP-SLN may be used as an alternative to BS in the treatment of rheumatoid arthritis in the future. The ultrasonic and pathological scores showed significant correlation in synovitis and bone erosion. Ultrasound can provide a useful assessment of synovitis in early arthritis.